Building Microservices with .NET Core 2.0 - Second Edition - Aroraa, Gaurav; Aroraa, Gaurav (Packt Publishing, 2017)
Architect your .NET applications by breaking them into really small pieces - microservices -using this practical, example-based guide.About This BookStart your microservices journey and get a broader perspective on microservices development using C# 7.0 with .NET Core 2.0Build, deploy, and test microservices using ASP.Net Core, ASP.NET Core API, and Microsoft Azure CloudGet the basics of reactive microservicesWho This Book Is ForThis book is for .NET Core developers who want to learn and understand the microservices architecture and implement it in their .NET Core applications. It's ideal for developers who are completely new to microservices or just have a theoretical understanding of this architectural approach and want to gain a practical perspective in order to better manage application complexities.What You Will LearnGet acquainted with Microsoft Azure Service FabricCompare microservices with monolithic applications and SOALearn Docker and Azure API managementDefine a service interface and implement APIs using ASP.NET Core 2.0Integrate services using a synchronous approach via RESTful APIs with ASP.NET Core 2.0Implement microservices security using Azure Active Directory, OpenID Connect, and OAuth 2.0Understand the operation and scaling of microservices in .NET Core 2.0Understand the key features of reactive microservices and implement them using reactive extensionsIn DetailThe microservices architectural style promotes the development of complex applications as a suite of small services based on business capabilities. This book will help you identify the appropriate service boundaries within your business. We'll start by looking at what microservices are and their main characteristics. Moving forward, you will be introduced to real-life application scenarios; after assessing the current issues, we will begin the journey of transforming this application by splitting it into a suite of microservices using C# 7.0 with .NET Core 2.0. You will identify service boundaries, split the application into multiple microservices, and define service contracts. You will find out how to configure, deploy, and monitor microservices, and configure scaling to allow the application to quickly adapt to increased demand in the future.With an introduction to reactive microservices, you'll strategically gain further value to keep your code base simple, focusing on what is more important rather than on messy asynchronous calls.Style and approachThis guide serves as a stepping stone that helps .NET Core developers in their microservices architecture. This book provides just enough theory to understand the concepts and apply the examples.